A Case of Prefemoral Fat Pad Impingement Syndrome Caused by Hyperplastic Fat Pad. (23rd December 2018) - Koyama, Suguru; Tensho, Keiji; Shimodaira, Hiroki; Iwaasa, Tomoya; Horiuchi, Hiroshi; Kato, Hiroyuki; Saito, Naoto
Abstract : Case . We report a rare case of prefemoral fat pad impingement syndrome that was caused by a hyperplasia of the normal suprapatellar fat pad. Pain and catching were observed in the proximal-lateral patellofemoral joint, and MRI imaging confirmed a hyperplasic mass in the same area. Although conservative treatment showed no signs of improvement, symptoms improved after an arthroscopic excision of the mass. Conclusion . Prefemoral fat pad impingement syndrome is related to patellar motion and should be considered as one of the underlying causes of anterior knee pain (AKP). Surgeons should recognize that a small hyperplasia composed of normal adipose tissue can cause AKP.